Land-use changes and geo-hydrological phenomena in the Abruzzo Periadriatic Area (central Italy): The case of the Pescara River basin - Giorgio Paglia; Vania Mancinelli; Ileana Schipani; Enrico Miccadei (Sustainable Environment)
Abruzzo Periadriatic Area (Central Italy) is sadly acknowledged as highly exposed to geo-hydrological hazards, with small-to-medium size catchments and urban areas strongly affected by natural phenomena. In the present work, the Pescara River basin, hit in the past by several floods and concurrent superficial landslides due to localized and intense rain events, has been studied. A screening of morphometry, land use changes, rainfall datasets, and flooding-related effects on landscape has been carried out, both at the catchment and local scales. A morphometric and geomorphological approach was applied, supported by GIS software and implemented with literature data. It allowed us to derive insights about the interaction between land use changes and geo-hydrological phenomena. Over the past 60 years, the study area underwent increases in built-up areas from ~16 km2 in 1955 to ~67 km2 in 2019 with significant sprawl at low altitude. Rainfall datasets outlined moderate-to-low annual precipitation with occasional heavy rainfall events (>100 mm/d and 30–40 mm/h). Historical and recent events (~35 events over a 100-year period) linked to landscape and geomorphological processes were also counted. Resulting data allowed to implement knowledge about the present-day geomorphological arrangement of the basin, providing information for land management in a changing environment. These findings provide valuable insights for future urban planning, policy formulation, and sustainable development initiatives, readily available to interested stakeholders.